Advances in Automotive Production Technology – Digital Product Development and Manufacturing: Stuttgart Conference on Automotive Production (SCAP2024) (ARENA2036, 2025)
This open access book compiles the outcome of the 3rd Stuttgart Conference on Automotive Production (SCAP2024). The peer-reviewed contributions in this book are arranged thematically in four parts and cover a wide variety of topics: (A) Digital Methods and Models, (B) Digitalization of the Industrial and Automotive Value Chain, (C) Data-Driven Technologies, and (D) Sustainability and Circular Economy. SCAP2024 was organized by ARENA2036 in close collaboration with the Institute for Control Engineering of Machine Tools and Manufacturing Units of the University of Stuttgart. The conference took place on site from November 20–22, 2024, and provided the opportunity for national and international scientists to present their latest research results. The conference has taken another big step in becoming an established forum for topics related to the production and mobility of the future. The great success of this year's conference will be continued with the next SCAP in 2026 with new forward-looking topics